Evidence for an ancestral founder of the common R116W mutation in the hydroxymethylbilane synthase gene in acute intermittent porphyria in the netherlands - de Rooij, F W M; Kavelaars, F G; Koole-Lesuis, H; Wilson, J H P (Cellular and Molecular Biology, 2009)
Acute intermittent porphyria (AIP), the most common acute hepatic porphyria, is an autosomal dominant inborn disorder of heme biosynthesis caused by mutations in the porphobilinogen deaminase (PBGd) gene. The prevalence of AIP in Europe is estimated as 1/10.000-1/20.000. The majority of the known AIP mutations are restricted to only one or just a few AIP families, with the exception of the frequent occurring R116W mutation which is found in 19/80 Dutch AIP families. This mutation has also been reported in 6 other populations (Sweden, Norwegian, i.a.) Recent haplotype analysis of Norwegian and Swedish patients with the R116W mutation show high heterogeneity. The conclusion of that report is that this mutation is abundant due a high mutability of CpG dinucleotides. The Dutch R116W families are well documented with extended pedigrees (up to 1750) which makes it possible to study the haplotypes in these families. To investigate haplotype heterogeneity in the Dutch R116W families. To investigate the haplotype heterogeneity of the Dutch R116W families, intragenic single nucleotide polymorphism'(SNPs) which cover the whole PBGd gene of 8.6 kb were selected. In addition to the intragenic SNPs, microsatellite markers were selected, flanking the genomic region of the PBGD gene covering a distance of 7.48cM in chromosome 11. The 7 SNPs were first analysed in 4 out of 19 R116W families selected for their most complete and informative pedigree. The 7 analysed SNPs revealed a distinctive R116W haplotype and were used to analyse the other 14 families in this study cohort, which mainly consisted of DNA from single patients or families with limited members. The informative SNPs reveal a distinctive haplotype which segregates with the R116W mutation present in the Dutch AIP families (-64T, 1345 G, 2479 G, 3581 G, 6479 T, 7064 C and 8578 A). SNP base nrs a less conserved microsatellite haplotype was observed in these AIP families. This common R116W haplotype based on 7 SNPs strongly suggests that the relatively high frequency of the R116W mutation in Dutch AIP patients is due a founder effect (eldest parent in pedigree was born in 1750!!). The high mutability of CpG dinucleotides is not a likely explanation for the abundant presence of the R116W mutation, since it is only reported in a few western countries. The heterogeneity described in the Sweden and Norwegian patients and the homogeneity found in the Dutch R116W carriers is compatible with origin of the mutation in Scandinavia with later introduction into the Netherlands. Due to the high frequency of this R116W mutation within the Dutch AIP families it may be applied to refine estimations of the prevalence of AIP in The Netherlands.